Elaboração de cerveja estilo saison adicionada de jabuticaba sabará (Myrciaria jaboticaba (Vell.) Berg) – capacidade antioxidante e caracteristica sensoriais - Carvalho, Matheus Pereira de (2021)
The growth in the number of microbreweries as well as beer related new products are the indicative of popularity and potential that this market has to absorb new revenues. The addition of fruit in beer is a centuries-old technique, with the purpose of adding new sensory characteristics to the product. The fruits used in this technique can add compounds capable of increasing beer’s stability and add interesting nutrients for the consumer. Jabuticaba is a fruit native to Brazil known for its pleasant sweet taste and high concentration of phenolic compounds in its peel and seeds. The aim of the following study was to develop and characterize a saison-style beer with the addition of jabuticaba Sabará (Myrciaria jaboticaba (Vell.) Berg). Four formulations were created with the addition of whole jabuticaba berries at different stages of the process (boiling and fermentation) and concentration (15 and 30%). The beers were divided into three groups: beers with the addition of jabuticaba during a boiling step (A and B) which are marked by their high composition of phenolic compounds and antioxidant activity, the aromas γ and α -eudesmol and ethyl octanoate (p <0.05); beers with jabuticaba added during fermentation (C and D), which are distinguished by their higher alcohol content, concentration of procyanidin B1 and the aromas of phenethyl alcohol, phenethyl acetate and decanoate (p <0.05); and the standard beer (P) characterized for the presence of catechin, succinic acid, bitterness (IBU) and the volatile compounds 9-hexadecanoate, 9-decanoate, ethyl hexanoate. During focus group beers with addition of jabuticaba were described with aroma of green leaves and peels and acidic, astringent and fruity herbal taste. The one preferred by the judges was beer C. These results lead to believe that the addition of jabuticaba during the boil step increases the concentration of phenolic compounds, thus the antioxidant capacity of the beers.